Front Cover: 4, 4‐Difluorospiro[2.2]pentan‐1‐yl – A Fluorinated Substituent To Expand the Synthetic and Medicinal Chemists' Toolbox (Eur. J. Org. Chem. 40/2022). Issue 40 (21st October 2022) - Melnykov, Kostiantyn P.; Voloshyna, Olena V.; Vashchenko, Bohdan V.; Demchuk, Oleksandr P.; Hryshchuk, Oleksandr V.; Grygorenko, Oleksandr O.
Abstract : The Front Cover shows novel 4, 4‐difluorospiro[2.2]pentan‐1‐yl building blocks as a promising combination of three‐dimensionality, conformational restriction, and gem ‐difluorination synthesized by Ukrainian chemists. The background photo by Mr. Bohdan Vashchenko shows the Kyїv Metro Bridge across the Dnipro River, connecting the Ukrainian capital′s left and right banks. The authors of the work often cross this bridge when moving between the buildings of Enamine and Taras Shevchenko National University of Kyїv, the two organizations they are affiliated with. The invaluable help of Ms. Vladyslava Prykhodko with artwork preparation is appreciated. More information can be found in the Research Article by O. O. Grygorenko et al .